Hubungan Dukungan Keluarga dengan Regulasi Diri Mahasiswa Perantau di Universitas Jambi - Alief Tarisa Putri; Fadzlul Fadzlul; Hanna Widya Gultom; Nofrans Eka Saputra (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Migrant students face various academic and psychological demands that require good self-regulation skills. One factor suspected to play a role in the formation of self-regulation is family support. This study aims to determine the relationship between family support and self-regulation in migrant students at the University of Jambi. The study used a quantitative approach with a correlational design. The study sample consisted of 147 migrant students at the University of Jambi selected using quota sampling techniques. Data collection was carried out using the Perceived Social Support from Family Scale (PSS-Fa) to measure family support and the Self-Regulation Scale to measure self-regulation. Data analysis was performed using the Pearson Product Moment correlation test. The results showed a significant positive relationship between family support and self-regulation in migrant students (r = 0.525; p = 0.001). These results indicate that the higher the family support received by students, the higher the level of self-regulation they have. In addition, the level of family support and self-regulation is mostly in the moderate category. These findings indicate that family support is a crucial factor in the ability of out-of-town students to manage their thoughts, emotions, and behaviors to achieve academic goals and adjust to life abroad. Therefore, family involvement through emotional, informational, reward, and instrumental support is essential to foster the development of student self-regulation.